Comparison of dual- and single-source dual-energy CT in head and neck imaging - May, Matthias; Wiesmüller, Marco; Heiß, Rafael; Brand, Michael; Brügel, Joscha; Uder, Michael; Wüst, Wolfgang (European Radiology, 2019)
Objectives: The aim of this study was to compare image quality of single-source dual-energy CT (SS-DECT) with third-generation dual-source dual-energy CT (DS-DECT) in head and neck cancer. Materials and methods: One hundred two patients with histologically proven head and neck cancer were prospectively randomized to undergo radiation dose-matched SS-DECT (n = 51, 120 kV, split-filter technique, 384 ref. mAs) or DS-DECT (n = 51, 80/Sn150 kV, tube A 100/tube B 67 ref. mAs). Inline default images (DI) and virtual monoenergetic images (VMI) for two different low energies (40 and 60 keV) were reconstructed. Objective image quality was evaluated as dose-normalized contrast to noise ratio (CNRD), and subjective image quality was rated on a 5-point Likert scale. Results: In both groups, highest CNRD values for vessel and tumor attenuation were obtained at 40 keV. DS-DECT was significantly better than SS-DECT regarding vessel and tumor attenuation. Overall subjective image quality in the SS-DECT group was highest on the DI followed by 40 keV and 60 keV. In the DS-DECT group, subjective image quality was highest at 40 keV followed by 60 keV and the DI. Forty kiloelectron volts and 60 keV were significantly better in the DS-DECT compared to the SS-DECT group (both p < 0.01). Conclusions: In split-filter SS-DECT as well as in DS-DECT, highest overall image quality in head and neck imaging can be obtained with a combination of DI and low keV reconstructions. DS-DECT is superior to split-filter SS-DECT in terms of subjective image quality and vessel and tumor attenuation. Key Points: • Image quality was diagnostic with both dual-energy techniques; however, the dual-source technique delivered significantly better results. • Highest overall image quality in head and neck imaging can be obtained with a combination of default images and low keV reconstructions with both dual-energy techniques. • The results of this study may have relevance for the decision-making process regarding replacement of CT scanners and focused patient examination considering image quality and subsequent therapeutic decision-making.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Diagnostic imaging; Head and neck neoplasms; Image enhancement